Valencia en Al-Mugrib fī hulà l-Magrib de Ibn Saʿīd al-Andalusī: Historia y literatura durante el periodo musulmán. - KACIMI, MOURAD (Scripta)
This article sheds light on the data on Valencia provided by Ibn Saʿīd al-Andalusī (1214-1286) in his work Al-Mughrib fī 'ulà l-Maghrib. First, we provide information on the author and his literary production, then we highlight the historical and literary value that his book provides. Then we analyze Ibn Saʿīd's version of the history of Valencia and compare it with other Arabic sources. In addition, we present and study literary texts of prose and poems chosen by the author to define and describe the city in the Islamic period (8th-13th centuries). On the other hand, we analyze the data that Ibn Saʿīd provides on the notable towns of the kingdom of Valencia, paying special attention to the Arabic toponyms and their possible meaning or origin. Finally, we analyze Ibn Saʿīd's criteria in selecting the prominent Arabic literary figures from each town of the kingdom of Valencia.